ONLINE LEARNING THROUGH LECTURE VIDEOS, GOOGLE MEET, POWERPOINT AND ITS IMPACT ON STUDENT OUTCOMES - Silvia Utami (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
This study aimed to investigate the students' view on the use of learning aids to support students in online learning such as lecture videos, PowerPoint, and Google Meet. It is also to investigate student outcomes by using lecture videos and other aids. The quantitative design is used with open-ended questions and Likert questions to get students' views related to the learning aids and summative assessment to know the student outcomes after using the learning aids. The number of students involved was 21 students of the English Literature Program at STBA Persada Bunda Pekanbaru in the 2021/2022 academic year. The study showed that most students found that lecture videos were the most helpful aid for them to support in comprehending the material followed by PowerPoint and Google Meet. Then, the student outcomes were better after studying from lecture videos and supported by PowerPoint and Google Meet. This study perhaps can shed some light on other lecturers using multiple media in delivering the material.